An Investigation Teaching Reading Strategies at SMA Negeri 3 Kota Ternate - Riska Grianti Hafel (JUPEIS : Jurnal Pendidikan dan Ilmu Sosial, 2023)
This research discussed about investigation teaching reading strategies. The aim of this research is to know the teacher’s use of teaching reading strategies at SMA Negeri 3 Kota Ternate. The researcher focuses on teaching reading strategies by teacher. The method of this research is qualitative by using descriptive analysis. The subjects of this research were two English teachers. The instruments used are observation, interview and documentation. Descriptive qualitative is used to analyzed and describe the data of the respondents. The results of this research show that there are several reading strategies that used by the teachers. Teacher A implemented four reading strategies, they include skimming, scanning, guessing the meaning of new words, and summarizing. Teacher B implemented two reading strategies they are guessing the meaning of new words and summarizing. The teaching reading strategies in the classroom used by the two teachers (A and B) indicated guessing the meaning of new words and sumarizing. Teaching reading strategies is very important to be applied to English Teachers. Because, it can make it easier for the students be able to read in English. Therefore, the researchers are very interested in conducting research related to the teaching reading strategies